Analysis of Students’ Learning Difficulties in Science on the Topic of Additive Substances at Junior High School - Sari, Lala; Enawaty, Eny; Sahputra, Rachmat (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study aims to describe students’ learning difficulties in science subjects on the topic of additive substances at SMP Swasta Sivaliputta Kubu Raya and to identify the factors contributing to these difficulties. The research employed a descriptive quantitative method, with data collected through questionnaires, unstructured interviews, observations, and documentation. The study involved 36 eighth-grade students as participants. The findings indicate that learning difficulties are influenced by internal factors, particularly study habits (49%), which fall into the category of “moderately experiencing difficulties.”This study recommends the implementation of interactive and contextual learning strategies, as well as the reinforcement of independent study habits, to improve students” understanding of science subjects, particularly the topic of additive substances.